PREFERENSI PEMILIHAN JEMBATAN SELAT SUNDA OLEH PENGENDARA MOBIL PENUMPANG - Maysyaroh, Fathonah; Joewono, Tri Basuki (FSTPT Indonesia, 2015)
Merak - Bakauheni is strategic of route for the movement between Java and Sumatraespecially for trips between Banten and Lampung. Data on the number of vehicles using the ferry transport between Banten - Lampung in the years 2000-2011 showed an average growth rate 5.99% per year. The purpose of this study is to build a model of infrastructure choice between toll bridge and ferry between Merak - Bakauheni using 'stated preference' techniques. This study develops model of infrastructure choice with variables of fare, travel time,waiting time, and the frequency of possibility of facility disruption. Study results show that waiting time and travel time have significant influence on the decision to choose infrastructure, while fare and possibility of disruption are found not significant. Study also found that Sunda Strait Bridge are selected by majority of respondent.